Removal of chromium with CNT coated activated carbon for waste water treatment - Kabbashi, Nassereldeen Ahmed; Nour, Abdurahman Hamid; Al-Khatib, Ma'an Fahmi Rashid; Maleque, Md. Abdul (Elsevier 2020, 2019)
Since the discovery of carbon nanotubes by Ijama in 1991, a researcher with the Nippon Electric Company (NEC) Laboratory in Tsukuba, Japan (Zhao et al., 2006) has been in the focus of material research due to their unique electronic and mechanical properties in combination with the chemical stability. Carbon nanotubes (CNTs) are nanostructures resulting from revolved graphene planes and have a range of attractive chemical and physical properties. CNTs exist as single (SWNTs), and multi-walled (MWNTs) structures. CNTs theoretically is well known of its high electrical conductivity, very high tensile strength, highly ﬂexibility where it can be bent considerably without damage, very elastic B18% elongation to failure, high thermal conductivity, low thermal expansion coefﬁcient, good ﬁeld emission of electrons and high aspect ratio (length to diameter ratio more than 1,000,000)